Acute dental periapical abscess and new-onset atrial fibrillation: A nationwide, population-based cohort study. (11th May 2021) - Hassan, A; Lip, G; Bisson, A; Herbert, J; Bodin, A; Fauchier, L; Harris, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: There are limited data on whether there is an association between hospitalisation with dental periapical abscess and new-onset atrial fibrillation (AF) which is independent of main cardiovascular risk factors. Purpose: To investigate whether there is an association between hospitalisation with dental periapical abscess and new-onset AF. Methods: A retrospective cohort study from a national database of patients hospitalised in 2013 (3.4 million patients) with at least five years of follow up, unless deceased. International Classification of Diseases (ICD) codes were used to compare the risk of developing new-onset AF for adults with and without dental periapical abscesses using univariate and multivariable analysis and hazard ratios (HR). Results: In total, 4, 693 patients classified as having dental periapical abscess, 435 (9.27%) developed AF, compared to 326, 241 (10.69%) without dental periapical abscess over a mean follow-up of 4.8 ± 1.7 years.  Multivariable analysis indicated that dental periapical abscess acted as an independent predictor for new onset AF (p < 0.01). Conclusions: An increased risk of new onset AF was identified for individuals hospitalised with dental periapical abscess. Careful follow up of patients with severe, acute dental periapical infections are needed for incident AF, as well as investigations of possible mechanisms linking these conditions.